VUV excited-state dynamics of cyclic ethers as a function of ring size. Issue 45 (11th November 2020) - Röder, Anja; Skov, Anders B.; Boguslavskiy, Andrey E.; Lausten, Rune; Stolow, Albert
Abstract : The ultrafast vacuum ultraviolet (VUV) Rydberg state dynamics of cyclic ethers reflects ring strain. Abstract : The vacuum ultraviolet (VUV) absorption spectra of cyclic ethers consist primarily of Rydberg ← n transitions. By studying three cyclic ethers of varying ring size (tetrahydropyran, tetrahydrofuran and trimethylene oxide, n = 6–4), we investigated the influence of ring size on the VUV excited-state dynamics of the 3d Rydberg manifold using time-resolved photoelectron spectroscopy (TRPES), time-resolved mass spectroscopy (TRMS) and ab initio electronic structure calculations. Whereas neither the electronic characters nor the term energies of the excited-states are substantially modified when the ring-size is reduced from n = 6 to 5 to 4, the excited-state lifetimes concomitantly decrease five-fold. TRPES and TRMS allow us to attribute the observed dynamics to a Rydberg cascade from the initially excited d-Rydberg manifold via the p-Rydberg manifold to the s-Rydberg state. Cuts through potential energy surfaces along the C–O bond reveal that a nσ* state crossing brings the s-Rydberg state along a path to the ring-opened ground state. The observed difference in excited-state lifetimes is attributed to an increasing slope along the repulsive C–O bond coordinate as ring size decreases.